Desain Perencanaan Pelaksanaan Pembelajaran Pendidikan Agama Islam Daring dengan Kurikulum Darurat - Astuty, Widy; Suharto, Abdul Wachid Bambang (Jurnal Penelitian Pendidikan Islam, 2021)
Teaching activities are the process of conveying knowledge information from teachers to learners. The success of the learning process will be achieved if it is based on established learning planning and healthy learning conditions. During the current Covid-19 pandemic, learning patterns have changed. The government enforces an emergency curriculum with the aim of continuing the learning process properly. The learning system changed which originally immediately became an online system. English translation. Of course, this also requires all teachers, including PAI teachers, to innovate in planning learning with an online system. This research was conducted to find out the process of how PAI teachers can design PAI learning planning that is in accordance with the pandemic situation based on the emergency curriculum that has now been implemented. The method is done by using descriptive qualitative. The techniques used are observation, interview and documentation directly to the process of designing learning planning by PAI teachers at SD N 1 Pageraji in Grade IV.